2016
DOI: 10.5455/aim.2016.24.394-396
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Value of Radiographic Union Score Hip Fracture after Treatment with Intramedullary Nail of Stable Hip Fractures

Abstract: Introduction:Given the importance of fracture healing on patient outcome in clinical practice, it is critical to assess fracture healing.Aim:The aim of this study was to evaluate the feasibility of the Radiographic Union Score Hip fracture after treatment with intramedullary nail of stable hip fractures.Patients and Methods:We retrospectively collected the data from the clinical records of our institution of the 47 patientswho had undergone intertrochanteric hip fracture treatment using an intramedullary nail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…A delay in union was found in three cases in group I and two cases in group II. When evaluated with RUSH scores, where reliability and validity studies have been carried out, 13 , 14 , 32 we found no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A delay in union was found in three cases in group I and two cases in group II. When evaluated with RUSH scores, where reliability and validity studies have been carried out, 13 , 14 , 32 we found no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 62%
“… 12 However, there are important variations in the evaluation of fracture healing in orthopaedic trauma studies. 32 When RUSH scores are used to evaluate union in femoral neck and intertrochanteric fractures, there was better agreement between radiologist and orthopaedist observers at the sixth months than at the third month. 14 In the present study, and for these reasons, delay in union was evaluated at the third month and RUSH scores obtained at the sixth month.…”
Section: Discussionmentioning
confidence: 97%
“…Studies in the literature have reported that not locking the nail distally reduces pain and bleeding and therefore the days of hospitalization. In the present study, we also have not locked the nails during the PFN procedure [28,29]. When durations of hospitalization were compared according to the operation types, the mean duration of hospitalization was significantly shorter in cannulated screw and PFN operations than in the other types of surgical procedures.…”
Section: Discussionmentioning
confidence: 70%
“…Multiple factors such as fracture type, patient comorbidities, surgical approach, and the type of IMN may affect the likelihood of nail breakage. [19][20][21][24][25][26] Subtrochanteric fractures, which occur in the area within 5 cm distal to the lesser trochanter, are prone to nonunion and malunion and require proper reduction before and during fixation to ensure favorable results. 6 Reasons for the breakage may also be attributed to excessive premature weight bearing or prolonged cyclical loading (eg, with nonunion).…”
Section: Discussionmentioning
confidence: 99%